Complexities of health and acceptance of electronic health records for the Austrian elderly population - Nicole Halmdienst; Gerald J. Pruckner; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2021)
We examine the personal health situation and how the complexities thereof affect the elderly Austrians' willingness to accept electronic health records (EHR). Using data from the sixth wave of the SHARE survey in Austria, we find the complexity of individual health problems and the social integration of individuals influencing the acceptance of EHR. The more the diagnoses of a patient, the more the medication she has to take, and the more often the treatment of a person in hospital, the higher is the acceptance of EHR. Having a chronic illness has a positive effect on EHR acceptance, whereas a pessimistic attitude and lack of joy in life, as indicators of depressive mood, have a negative impact. The results are mainly driven by females and younger patients aged between 50 and 70. People with poor social connection express lower acceptance of EHR.
Keywords: I11; I12; I18; 330; Electronic health records; health status; socíal connectedness; SHAREsurvey